MANFAAT HASIL BELAJAR MANAJEMEN BISNIS DESAIN MODE SEBAGI KESIAPAN MENJADI FASHION CONSULTANT PADA LAYANAN JASA FASHION AGENCY - Rieska Valinda Putri Delarisa; Winwin Wiana (Fesyen Perspektif, 2017)
This research investigates the benefits of learning mode design business manajement as a readiness to be fashion consultant in the fashion agency service. This knowledge and skills required to be fashion consultants in a fashion agency can be found and studied in the subject of Mode Design Business Management in Fashion Design Education DPKK FPTK UPI. The purpose of this research is to acquire the data of studying Mode Design Business Management result benefit as part of the preparation in becoming fashion consultant in a fashion agency. The methodology used in this research is descriptive methodology using questionnaires as the data collection tool. The population in this research is the students of Fashion Design Education DPKK FPTK UPI of year 20011-2012. The research results indicate that the majority of the respondents acknowledge the benefit of studying mode design business management as part of the preparation in becoming fashion consultant in a fashion agency.